Modelled frontal ablation and velocities at Kronebreen, Svalbard, are sensitive to the choice of submarine melt rate scenario - Felicity Alice Holmes; Eef van Dongen; Nina Kirchner (Journal of Glaciology)
Both submarine melt and calving are important for the overall mass balance of marine-terminating glaciers, but uncertainty is rife with regards to the magnitude of the processes. Modelling allows for these processes to be investigated without the need to visit inaccessible ice marginal zones. This study looks at the impact of different submarine melt and sea-ice back pressure scenarios on modelled calving activity and dynamics at Kronebreen, Svalbard, by running separate summer and winter simulations with various submarine melt parameterisations and sea-ice characteristics. It is found that submarine melt is an important driver of seasonal variation in modelled glacier dynamics and calving activity, with the choice of sliding law also exerting a significant influence on results.